Effect of Product Quality, Promotion, Brand Image on Sales Increase: Pengaruh Kualitas Produk, Promosi, Brand Image Terhadap Peningkatan Penjualan - Royani, Mochamad Allim Uddin Rizal; Prapanca, Detak (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine that product quality, promotion, and brand image have a simultaneous effect on increasing sales. The Covid-19 pandemic has had a huge impact on Indonesia, especially in the economic sector. Not only in the economic sector, but the Covid-19 pandemic has an impact on the education and office sectors of this country. In this study using quantitative methods. Meanwhile, the data analysis technique used in this research is data quality test, classical assumption test, and multiple linear regression analysis.